# How do you solve #4x - ( x - 1) = 2x + 7#?

Prior to combining like terms on the right side of the equation, expand the terms enclosed in parenthesis, keeping in mind the signs:

By signing up, you agree to our Terms of Service and Privacy Policy

To solve ( 4x - (x - 1) = 2x + 7 ), follow these steps:

- Distribute the negative sign inside the parentheses: ( 4x - x + 1 = 2x + 7 ).
- Combine like terms: ( 3x + 1 = 2x + 7 ).
- Subtract ( 2x ) from both sides: ( 3x - 2x + 1 = 7 ).
- Simplify: ( x + 1 = 7 ).
- Subtract 1 from both sides: ( x = 6 ).

So, the solution is ( x = 6 ).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7